(untitled) (Research, Society and Development, 2023)
Edentulism is a current problem that afflicts the Brazilian population. In this sense, oral rehabilitation techniques have evolved, with the aim of getting as close to natural as possible. Therefore, fixed rehabilitations on implants in completely edentulous patients appear as a satisfactory way to overcome the limitations of mucous-supported prostheses, characterized by parsimony in retention and stabilit. The objective was to carry out a narrative review of the current scientific literature regarding rehabilitation with fixed prosthesis on implants in completely edentulous patients. The search for articles was carried out using the databases PubMED/Medline, LILACS, BVS and SCIELO, using the descriptors: Oral rehabilitation AND Fixed prothesis AND Protocol AND Dental implants. Articles referring to the last ten years were included, which fit and presented characteristics relevant to the objectives of the work, without language restrictions. It was evidenced in the articles that biomechanics is a complicating factor in this type of rehabilitation, and the number of implants in the arch must be adequate to the bone quality of each patient. Diagnostic assembly is essential for this type of rehabilitation, with the presence of lip support being a key factor for indicating or not this technique. The psychological aspects were evidenced as a highly positive factor for the patients, due to greater mechanical stability, functionality, phonetics and aesthetics. The rehabilitation of toothless patients with the protocol prosthesis involves complex and complicating aspects, it is necessary for the rehabilitator to be fully updated to provide the best to each patient.